Measurement of Indoor and Outdoor Background Ionising Radiation Levels of Kwali General Hospital, Abuja - IU James; IF Moses; JN Vandi; UE Ikoh (Journal of Applied Sciences and Environmental Management, 2015)
Measurement of indoor and outdoor background ionising radiation level at Kwali General Hospital, Abuja, Nigeria was carried out using a well calibrated Geiger muller counter; Atomtex AT1117M radiation monitor. The dose equivalent results obtained range from 0.100±0.001 ìSv/h to 0.124±0.007 µSv/h with an average of 0.107±0.003 ìSv/h for indoor measurement while it ranges from 0.100±0.001 µSv/h to 0.122±0.003 µSv/h with an average of 0.108±0.003 µSv/h for outdoor measurement respectively. The obtained values are below the standard background radiation of 0.133 µSv/h. The study also revealed that the average annual equivalent dose rate is 0.750± 0.020 mSv/y and 0.189±0.005 mSv/y for indoor and outdoor measurements respectively. These results revealed that the dose levels in all of the locations (indoor and outdoor) were below the 1 mSv/y maximum permissible limit for the public set by International Commission on Radiological Protection (ICRP). Therefore, Kwali General Hospital is radiologically safe ©JASEM